Satisfaction and complications with the Titan® one-touch release penile implant. (February 2014) - Lindeborg, Lisa; Fode, Mikkel; Fahrenkrug, Lasse; Sønksen, Jens
Abstract: Objective. The aim of this study was to assess complication rates and patient satisfaction with Coloplast Titan® one-touch release (OTR) inflatable penile implants inserted at one university hospital centre between November 2008 and April 2011. Material and methods. Overall, 33 patients with organic erectile dysfunction underwent penile implant surgery during the study period. The Titan OTR inflatable penile implants were inserted using a penoscrotal approach. Patient and partner satisfaction was assessed with the Erectile Dysfunction Inventory of Treatment Satisfaction (EDITS) questionnaire. Results. One implant was removed because of infection, and three patients underwent revision surgery due to problems with autoinflation, deflation, and a displaced reservoir, respectively. In all cases the problems were solved and the implants were salvaged. Further complications included one patient with haematoma and sustained scrotal pain, one patient with meatal stenosis, and four patients with infections not related to the implant. In total, 30 EDITS questionnaires were administered and 26 (87%) were completed. Twenty-two patients (85%) reported being satisfied with the implant and two (8%) were dissatisfied. Twenty-four patients (92%) would recommend a penile implant to someone with a similar medical condition. Eighteen patients (72%) believed that their partner was satisfied with the implant. Nineteen patients (76%) felt that the process of achieving an erection with the implant was natural. Conclusion. Although it is important to inform patients about potential problems such as infection, pain and mechanical failure, the results show that inflatable penile implants are a good treatment choice for erectile dysfunction when conservative measures have failed.